Kinerja keuangan dan pengaruhnya terhadap penghindaran pajak - Pratiwi, Ratna; Ratnawati, Juli (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This research was conducted to test the influence of financial performance in terms of profitability, leverage, and liquidity. This research was applied to coal industry companies listed on the Indonesian Stock Exchange (IDX) in the range of 2018 to 2021. The sample collection used a purposive sampling method with certain criteria and obtained a sample of 19 companies with a total of 50 observational data points. In this study, multiple linear regression analysis was used as a data analysis method. The results of this study show that profitability, leverage, and liquidity all contribute to tax avoidance simultaneously, while partially obtaining the results of profitability affects tax avoidance, leverage and liquidity don’t affect tax avoidance. So that companies in carrying out tax avoidance can maximize the limitations on profitability results obtained in the company's business activities by also paying attention to the value of leverage and liquidity in the company.